Ilustración biográfica de personajes célebres de Riobamba mediante una serie de colección dirigido a niños de 10 a 12 años de la ciudad de Riobamba. - Cuenca Sarango, Viviana Patricia (2017)
The present research comes from the lack of knowledge about the life of the different famous characters of the city of Riobamba. Children, young people and even adults do not know much of this topic. This maybe happens due to the scarcity of illustrated publishing products that encourage reading, so illustration is major tool for captivating reader’s attention. The quasi-experimental method was applied because it allowed giving greater strength to the proposal which tries to solve the problem of certain form offering illustrations of high quality. It was necessary to analyze in a theoretical way the characteristics and the processes to generate a correct infantile illustration. In addition, each of the important aspects of the life of these famous characters was analyzed bibliographically. The editorial product aims to raise awareness about the importance of knowledge of the biography of these famous characters, because it helps to generate a greater local and historical identity.